PENATALAKSANAAN HOLISTIK PASIEN PADA PEREMPUAN USIA 25 TAHUN DENGAN ASMA PERSITEN RINGAN BERBASIS LAYANAN KEDOKTERAN KELUARGA DI WILAYAH KERJA PUSKESMAS KEDATON - Sari, Zada Amalia Agatha; Susanto, Eko Budi (CV. Jasa Sukses Abadi, 2025)
Asthma is a heterogeneous disease, characterized by chronic inflammation of the airways characterized by a history of respiratory symptoms such as wheezing, shortness of breath, chest tightness, and coughing that vary in time and intensity, accompanied by variations in expiratory airflow obstruction. The purpose of this study is to apply a holistic and comprehensive family medicine approach in detecting internal and external risk factors and solving problems based on Evidence Based Medicine which is a family approach, patient-centered, community oriented. This research method uses a descriptive study of case reports. Primary data were obtained through autoanamnesis, physical examination, and home visits to patients. Secondary data were obtained from patient medical records at the Kedaton Health Center. The assessment was carried out based on a holistic diagnosis from the beginning, process, and end of the study quantitatively and qualitatively. The results obtained were that patient Ms. S, 25 years old, diagnosed with mild persistent asthma was managed comprehensively, namely given medication in the form of bronchodilators and inhalers and carried out interventions using poster media and showing asthma exercise videos. The evaluation showed that the results were in the form of improved patient complaints, increased understanding of the disease as evidenced by a comparison of pre- and post-test values, and increased family support. The conclusion obtained was that the application of a family doctor approach was needed for holistic and comprehensive management of patients with mild persistent asthma to detect internal and external risk factors in order to support the success of therapy and improve the patient's quality of life.